2015
DOI: 10.17116/oftalma2015131334-44
|View full text |Cite
|
Sign up to set email alerts
|

Results of the use of antioxidant and angioprotective agents in type 2 diabetes patients with diabetic retinopathy and age-related macular degeneration

Abstract: Extended analysis of clinical, functional and morphological changes in the retina at the onset of DR in type 2 diabetes patients with concomitant "dry" AMD enables timely diagnosis, prognosis, prevention, and early treatment. Conservative treatment with antioxidant and angioprotective agents has been proved effective in type 2 diabetes patients with preclinical (DRO) and early (DR1) diabetic retinopathy and those with DR and "dry" AMD (AREDS 1-3) in terms of functional and morphological parameters of the retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Despite a good body of positive experimental data, clinical trials using antioxidants, in contrast, have not been conclusive. Analysis of clinical, functional and morphological changes in the retina in type 2 diabetic patients with early retinopathy has demonstrated beneficial effects of treatment with antioxidant and angioprotective agents [98]. A double masked, placebo controlled clinical trial on limited number of diabetic patients (<70 patients) has shown some meaningful improvements in the visual function using a multi-component nutritional formula consisting of vitamins C, D3, and E, zinc oxide, eicosapentoenoic acid, docosahexaenoic acid, alpha-lipoic acid, coenzyme Q10, zeaxanthin, lutein, benfotiamine, N-acetyl cysteine, resveratrol, turmeric root extract, green tea leaf [99].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Despite a good body of positive experimental data, clinical trials using antioxidants, in contrast, have not been conclusive. Analysis of clinical, functional and morphological changes in the retina in type 2 diabetic patients with early retinopathy has demonstrated beneficial effects of treatment with antioxidant and angioprotective agents [98]. A double masked, placebo controlled clinical trial on limited number of diabetic patients (<70 patients) has shown some meaningful improvements in the visual function using a multi-component nutritional formula consisting of vitamins C, D3, and E, zinc oxide, eicosapentoenoic acid, docosahexaenoic acid, alpha-lipoic acid, coenzyme Q10, zeaxanthin, lutein, benfotiamine, N-acetyl cysteine, resveratrol, turmeric root extract, green tea leaf [99].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Nonetheless, a deep knowledge of AMD pathogenic mechanisms is still lacking so far, which complicates the establishment or approval of effective treatment strategies. While the overactive angiogenesis and visual deficits occurring in wet AMD can be mitigated by anti-VEGF drugs, this is not the case for dry AMD [ 45 ] Recent evidence-based studies show that dietary phytochemicals such as lutein/zeaxanthin, resveratrol, and Vaccinium myrtillus may be beneficial in retinal diseases including AMD [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. In general, these compounds have been claimed to interfere with the biology of disease by mitigating oxidative stress and inflammation, which play a critical role in the initiation and progression of AMD [ 47 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lutein and zeaxanthin, which are also called macular xanthophylls, show their effects by filtering high energy visible light, mostly with a peak of absorption at 446 nm and ultraviolet radiation lesser, inhibiting lipid peroxidation and reducing reactive species such as singlet oxygen and hydroxyl radical [46][47][48]. These carotenoids have several benefits on human health, including neuroprotective effects [49][50][51], anti-carcinogenic effects [52][53][54][55], anti-diabetic effects [56][57][58], cardioprotective effects [59][60][61], protective effects on skin damages and ocular diseases [62][63][64][65]. Particularly, several studies showed the role of lutein and zeaxanthin in eye diseases.…”
Section: Introductionmentioning
confidence: 99%